2022
DOI: 10.1101/2022.12.09.519754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational restriction shapes inhibition of a multidrug efflux adaptor protein

Abstract: Membrane efflux pumps play a major role in bacterial multidrug resistance. The tripartite multidrug efflux pump system from Escherichia coli, AcrAB-TolC, is a target for inhibition to lessen resistance development and restore antibiotic efficacy, with homologs in other ESKAPE pathogens. Here, we rationalize a mechanism of inhibition against the periplasmic adaptor protein, AcrA, using a combination of hydrogen/deuterium exchange mass spectrometry, cellular efflux assays, and molecular dynamics simulations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Previously, we proposed a mechanism for the AcrA efflux pump inhibitor (EPI) NSC 60339. 12 Using a combination of HDX-MS, MD simulations and cellular efflux assays, we suggested that NSC 60339 acts as a molecular wedge between the lipoyl and αβ barrel domains of AcrA, reducing its structural dynamics across all four domains. Our previous work utilised HDX-MS investigations at pH 6.0, reflecting the often more acidic conditions of the periplasmic environment, where AcrA resides.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, we proposed a mechanism for the AcrA efflux pump inhibitor (EPI) NSC 60339. 12 Using a combination of HDX-MS, MD simulations and cellular efflux assays, we suggested that NSC 60339 acts as a molecular wedge between the lipoyl and αβ barrel domains of AcrA, reducing its structural dynamics across all four domains. Our previous work utilised HDX-MS investigations at pH 6.0, reflecting the often more acidic conditions of the periplasmic environment, where AcrA resides.…”
Section: Resultsmentioning
confidence: 96%
“…Wild type, lipidated AcrA, was used for all functional assays and a previously established functional and soluble AcrA construct (AcrA s ), with its lipidation site removed by mutation, was used for structural and biophysical investigations as it provided the required sample homogeneity. 12,20 This delipidated AcrA construct was also utilized for MD simulations, with (de)protonation of the unique His285 residue used as a proxy for pH 7.4 and 6.0 conditions. His285 is located at the αβ barrel domain surface facing the lipoyl domain and is the only residue within AcrA that has a titratable protonation state change between mildly acidic and neutral regimes (with a pKa ∼6) ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of computational (ensemble docking) and experimental approaches (in vitro AcrA binding studies using surface plasmon resonance, as well as in vivo limited proteolysis) suggested that both compounds target AcrA, the MFP/PAP component of the tripartite AcrAB-TolC complex. NSC60339 is thought to bind to the hinge region (linking α-hairpin-and lipoyl-domains) of AcrA, thereby constricting conformational flexibility and reducing its ability to transduce signal to AcrB possibly inhibiting functional rotation and efflux [182]. NSC33353, however, is suggested to bind the AcrA membrane proximal (MP) domain (Fig.…”
Section: Inhibitors Acting Against Rnd-type Efflux Pumps From Enterob...mentioning
confidence: 99%
“…The same complex is a target for inhibition to interfere with resistance development and restore antibiotic efficacy. MS analyses of this complex furnished molecular insights into multidrug adaptor protein function which could be useful for the development of new antimicrobial therapeutics [49].…”
Section: Hydrogen-deuterium Exchange Mass Spectrometry(h/dx-ms)mentioning
confidence: 99%